The Relationship between Electricity Energy Consumption and Income: Evidence from ARDL Bounds Testing for Kyrgyz Republic - Hali̇s, Muhsin; Korap, Levent (International Review of Economics and Management, 2016)
The potential links between energy consumption and real income have a critical role in designing discretionary macroeconomic policies for stabilization purposes. In this paper, we try to examine such a relationship for Kyrgyz Republic, and utilize some contemporaneous time series estimation techniques to obtain policy-based conclusions. In light of a methodological discussion, the results indicate that there exists a long run relationship if the real income is chosen as the dependent variable. We found that the larger the electricity consumption the larger would be the real income. Also, the causality analyses carried out in a Granger sense do not support the so-called neutrality hypothesis which means no causal relations between the variables. Instead, we give evidence supporting a one-way causality running from changes in electricity consumption to changes in real income. All in all, the paper emphasizes that policies in favor of energy conservation can lead to harm the economic growth in Kyrgyz Republic.
Keywords: Energy Consumption; Real Income; ARDL Bounds Testing; Causality; Kyrgyz Republic; 8. Economic growth; 1. No poverty; 7. Clean energy